Fine structure of the compound eyes of the crepuscular moth Grapholita molesta (Busck 1916) (Lepidoptera: Tortricidae) - Yang, Xiaofan; Ran, Hongfan; Jiang, Yueli; Lu, Ziyun; Wei, Guoshu; Li, Jiancheng (Frontiers in Physiology, 2024)
Morphological organization, ultrastructure and adaptational changes under different light intensities (10000, 100, 1, and 0.01 mW/m 2 ) of the compound eye of the oriental fruit moth Grapholita molesta (Busck 1916) were investigated. Its superposition type of eyes consist of approximately 1072 ommatidia in males and 1029 ommatidia in females with ommatidial diameters of around 15 μm. Each ommatidium features a laminated corneal lens densely covered by corneal nipples of 256 nm in height. Crystalline cones are formed by four cone cells, proximally tapering to form a narrow crystalline tract with a diameter of 1.5 μm. Eight retinula cells, two primary and six secondary pigment cells per ommatidium are present. The 62.3 μm long rhabdom is divided into a thin 1.8 μm wide distal and a 5.2 μm wide proximal region. Distally the fused rhabdom consists of the rhabdomeres of seven retinula cells (R1-R7) and connects with the crystalline cone. In the proximal rhabdom region, the pigment-containing retinula cell R8 occupies a position in centre of the rhabdom while R1-R7 cells have taken peripheral positions. At this level each ommatidial group of retinula cells is surrounded by a tracheal tapetum. In response to changes from bright-light to dim-light adaptations, the pigment granules in the secondary pigment cells and retinula cells migrate distally, with a decrease in the length of crystalline tract.